ANALISIS PERBANDINGAN KINERJA PERANGKAT BAHAN BAKAR PLTN TIPE PWR AP 1000 DAN PWR 1000 MWe TIPIKAL DENGAN MENGGUNAKAN PROGRAM KOMPUTER - Arif Nurmawan; Suroso Suroso; Harto Tanujaya (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Investigation of fuel element thermal-hydraulic characteristic is important step related to aspect of fuel bundle reactor design. This paper analyzes of the PWR AP1000 and PWR 1000 MWe Typical of fuel bundle thermal-hydraulic using RELAP5 code. Choosing PWR AP 1000 and PWR 1000 MWe Typical because the both of them have almost same power that is 3400 MWth and 3410 MWth but have differences on fuel bundle sum, the high of active core, and rod diameter. On the fuel bundle, there are 17x17 fuel rods that have a radial factor the power varies. Modelling of fuel bundle are divided into 4 channel groups, ie. power factor of 1.396, range power factor of 1.203 to 1.394, power factor of le then 1.198 down and bypass channel. Axially, the channels are divided into 3 zones there are stand-off assembly at the bottom, an active length of the channel and the zone of upper plenum. The active length divided into 10 axial nodes. The goal of this analysis is fuel bundle design validation of PWR AP 1000 and PWR 1000 MWe Typical and get thermal-hydraulic comparison for steady-state condition. The analysis result including cooling floe rate, axial temperature distribution of cladding and cooling temperature, heat flux and pressure drop. In steady condition, the model was verified with the parameter of AP-1000 and PWR 1000 thermal-hydraulic design in which shows a good agreement. Verification results show that the model is made still need refinement, however qualitatively within realistic limits. Further updating of the model will be done to get a better verification results.